Determination of relative dissociation energy from electro-optics as a new single-proposed parameter of vegetable oil quality - Ketut Sofjan Firdausi; Izzah Afiefah; Heri Sugito; Ririn Widya Septianti; Very Richardina; Qidir Maulana Binu Soesanto; Much Azam (Diponegoro University Semarang Indonesia, 2019)
In this report, we study the electro-optics effect on cooking oil to obtain the relative dissociation energy as a new single proposed parameter of oil quality. The sample was canola oil which had been heated in 0.5 hours, 2 hours and 4 hours. The light source used in the experiment was a green pointer laser with a wave length of 532 nm. The sample was applied to a potential difference from 0 to 9 kV to obtain the electro-optics effect in form of the change of the polarization angle Dq as function of potential difference DV. The relative dissociation energy was obtained from the fitting data of the relative Lenard-Jones potential energy curves represented by change of polarization per unit change of potential difference, Dq/DV. The result shows that the relative dissociation energy is reduced as the oil quality decreased after heated. The relative dissociation energy provides simple physical understanding about electro-optics effect on cooking oils. The study of electro-optics polarization that represents relative Lenard-Jones potential energy is a new but somewhat intuitive, which can be further improved and emphasized for grouping, mapping, and determining various cooking oil quality and halal food due to the lard contamination.